Doctors, Discipline, and the Death Penalty: Professional Implications of Safe Harbor Policies - Sawicki, Nadia N (2015)
Of the thirty-seven U.S. jurisdictions that authorize the use of capital punishment, all but one use lethal injection as an execution method. Nearly every jurisdiction's lethal injection procedures permit or require the presence or participation of a physician or other licensed medical provider. Moreover, courts throughout the country have recognized the Eighth Amendment implications of lethal injections administered by personnel without adequate medical training. A prisoner may suffer pain so excruciating as to constitute cruel and unusual punishment if execution technicians encounter any one of a number of potential problems-if they have difficulty placing the intravenous (IV) line by which the necessary drugs are delivered; improperly prepare the drugs, modify their quantities, or administer them in the wrong order; fail to accurately assess the prisoner's anesthetic depth; or are faced with any medical anomaly or emergency that necessitates deviation from standard procedures